the political activism of Rafael Correa on Twitter during the Ecuadorian sectional elections of 2019 - Rubio Mantilla, Irina Salomé; Robby Santillán, Darío Gilberto; Márquez Domínguez, Carmelo (SATHIRI, 2022)
From the point of view of mass and global communication, social networks have nowadays become daily, fundamental and essential tools in all kinds of ways, used by celebrities, politicians and ordinary citizens, in order to be close to the public / society and for a permanent, almost instantaneous interaction. In this sense, these networks of social media contribute to the current political system a series of new elements immersing the political marketing; undoubtedly, it is an informative source from which all agendas are built (public, media, political. The objective of this research is to demonstrate the - still - strong presence and influence of Rafael Correa Delgado in Ecuadorian political activity, through Twitter (@MashiRafael): his current “workhorse” from which he generates opinion, discussion and political analysis. In this academic work, the impact of this social media will be analyzed during the sectional elections of 2019, in a strategic observational period that includes the first week of the campaign (from February 5 to 11) and the last week of the voting (from 18 to March 24) through the application of a mixed (qualitative-quantitative) methodology from which diverse and numerous datas were extracted that enabled an in depth knowledge on various topics, actors, frames and statistics on the messages issued by the subject of the investigation. Likewise, once all the information was collected, a consequent comparison was made with the 24 Hours of Teleamazonas news (in its evening and night editions) of the mentioned dates, in order to observe its impact on the media agenda.